WACANA KOMPARASI PERADABAN BARAT DAN TIMUR DI INDONESIA - Eka Susanti (Universitas Islam Negeri Sumatera Utara, 2016)
History is narrated discourse rationalism and empiricism is an effective tool for passing identity in Western society. But the impact will be destructive when used in Eastern societies, such as criticism Henk Schulte Nordholt that Indonesia's history is a history without people and people without history. It meant that, the public has felt that the story of the past, including culture, which was written by an academic historian is not about them. As a result of the mistrust, people drain their life without an identity and a clear direction as well as other criticism is the discourse of historical determinism Indonesia trapped in the West.Keywords: Discourse, eastern and western civilization